Partial characterization of a biosurfactant extracted from Pseudomonas sp. B0406 that enhances the solubility of pesticides. Issue 20 (18th October 2018) - García-Reyes, Selene; Yáñez-Ocampo, Gustavo; Wong-Villarreal, Arnoldo; Rajaretinam, Rajesh Kannan; Thavasimuthu, Citarasu; Patiño, Rodrigo; Ortiz-Hernández, Ma Laura
ABSTRACT: Biodegradation of some organochlorine and organophosphate pesticides is difficult because of their low solubility in water and, therefore, their low bioavailability. To overcome the hydrophobicity problem and the limited pesticide availability, biosurfactants play a major role. In this study, we evaluated the effect of an extract from Pseudomonas sp. B0406 strain with surfactant properties, on the solubility of two pesticides: endosulfan (ED) and methyl parathion (MP). Such a process was performed in order to increase the aqueous solubility of both pesticides, to increase its availability to microorganisms and to promote their biodegradation. The extract from Pseudomonas sp. B0406 showed a critical micellar concentration of 1.4 g/L and the surface tension at that point was 40.4 mN/m. The preliminary chemical and physical partial characterization of the extract with surfactant properties indicated that it is an anionic glycolipid, which increases the solubility of both pesticides of 0.41 at 0.92 mg/L for ED and of 34.58 at 48.10 mg/L for MP. The results of this study suggest the effectiveness of this extract in improving the solubility of both pesticides ED and MP in water and, therefore, of its potential use to enhance the degradation of these pesticides.